Human Chorionic Gonadotropin monotherapy for the treatment of hypogonadal symptoms in men with total testosterone > 300 ng/dL - Madhusoodanan,Vinayak (2019)
ABSTRACT Purpose The 2018 American Urological Association guidelines on the Evaluation and Management of Testosterone Deficiency recommended that 300 ng/dL be used as the threshold for prescribing testosterone replacement therapy (TRT). However, it is not uncommon for men to present with signs and symptoms of testosterone deficiency, despite having testosterone levels greater than 300 ng/dL. There exists scant literature regarding the use of hCG monotherapy for the treatment of hypogonadism in men not interested in fertility. We sought to evaluate serum testosterone response and duration of therapy of hCG monotherapy for men with symptoms of hypogonadism, but total testosterone levels > 300 ng/dL. Materials and Methods We performed a multi-institutional retrospective case series of men receiving hCG monotherapy for symptomatic hypogonadism. We evaluated patient age, treatment indication, hCG dosage, past medical history, physical exam findings and serum testosterone and gonadotropins before and after therapy. Descriptive analysis was performed and Mann Whitney U Test was utilized for statistical analysis. Results Of the 20 men included in the study, treatment indications included low libido (45%), lack of energy (50%), and erectile dysfunction (45%). Mean testosterone improved by 49.9% from a baseline of 362 ng/dL (SD 158) to 519.8 ng/dL (SD 265.6), (p=0.006). Median duration of therapy was 8 months (SD 5 months). Fifty percent of patients reported symptom improvement. Conclusions Treatment of hypogonadal symptoms with hCG for men who have a baseline testosterone level > 300 ng/dL appears to be safe and efficacious with no adverse events.